Simulation Analysis of Ring Chain Drive of Heavy Scraper Conveyors Based on Adams - Zhu Feng; Wang Peng (Jixie chuandong)
Ring chain is the most important part of the scraper conveyor, whose motion characteristics directly affect the capacity and efficiency of the conveyor. Sprocket chain ring of SGZ 1000/3*1000 scraper conveyor is selected as the research object to analyze characteristics of circular chain drive of heavy scraper conveyors. The ring chain drive system is modeled using the SolidWorks software. The kinematics and dynamics simulation of the meshing process of the sprocket and chain ring under different working conditions are carried out using the Adams software. The influence of different working conditions on the ring chain drive system of the scraper conveyor is analyzed. The results show that the deformation of the ring chain and the fluctuation of the load lead to the relative sliding of flat rings in meshing contact, which is the main cause of chain socket wear. Different rotational speeds will affect the stability of the ring chain transmission. Under normal operating conditions, when the speed is maintained at 1.8 m/s, the chain transmission is relatively stable. The results could provide a theoretical foundation in optimizing the design of ring chains of heavy scraper conveyors.